Phytochemical and biological studies on paulownia tomentosa (Thunb.) steud. family scrophulariaceae growing in Egypt - Esraa Abdelhamid Refaat; Nabaweya Ali Ibrahim; Seham Salah Eldin Eelawary (Cairo : Esraa Abdelhamid Refaat, 2013)
This thesis aimed to the discovery of therapeutic agents derived from Paulownia tomentosa (Thunb.) Steud.Family Scrophulariaceae by carrying out an applied pharmacognostical study including extraction, isolation and identification of the biologically active constituents. We are looking to reach safe and effective therapeutic agents from botanical origin which can be useful in drug industry.
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacognosy
Issued also as CD
Keywords: Essential oil; Paulownia tomentosa (Thunb.) Steud; Scrophulariaceae